Powdered Activated Carbon (PAC)-Ceramic Composite Adsorbent for Iron and Aluminum Cations Removal from Acid Mine Drainage - Tine Aprianti; Tuti Indah Sari; Fitri Hadiah; Yadi Utama; Muhammad Said (Institute for Research and Community Services, Institut Teknologi Bandung, 2022)
Acid mine drainage has become a serious problem globally, polluting groundwater with heavy metals. Adsorption is considered a simple and effective approach to addressing this emerging issue. A commonly used adsorbent is powdered activated carbon (PAC), but this is susceptible to being washed into the waste stream, either during or after the adsorption process due to its low density. This research combined PAC with clay that was molded into small clay balls ( 1 cm in diameter) then baked at a very high temperature of 1000 °C to create a ceramic adsorbent. The adsorbent activation used NaOH 48% alkali solution to improve its capability in binding metallic cations. This research demonstrated that the PAC-ceramic composite is an efficient adsorbent for the removal of Fe (iron) and Al (aluminum) cations from acid mine drainage. The results showed that the most favorable contaminant removal was 60.87% for Fe and 52.13% for Al, using a PAC:clay ratio of 45:55 (w/w) in 10 hours contact time.